School support, motivation and use of contextual teaching among secondary school agriculture teachers - Abdul Latir, Siti Shuhaidah; Hamzah, Ramlah; Mat Rashid, Abdullah (IDOSI Publications, 2014)
Agriculture education is more than presenting a material as agriculture sector is becoming more technological, specialized and efficient. Agriculture science teachers face the slow adjustment of agricultural education programs and problem in choosing effective teaching and instructional strategies. There is a need of agriculture science teacher to use different teaching approaches such as contextual teaching to improve previous teaching practice which only accentuates on students’ knowledge transfer for examination preparation and allows students to connect education with their life. The purpose of this study is to identify the relationship between perceived school support, motivation and use of contextual teaching among secondary school agriculture teachers. This study used a quantitative approach with mail as a method for data collection. The subjects of this study were drawn randomly to make a sample of 280 secondary school agriculture teachers in Malaysia. Results have shown that secondary school agriculture teachers have high level of perceived school support, positive motivation towards contextual teaching and have high level of perceived used of contextual teaching. In addition, there was a significant relationship between secondary school agriculture teachers’ perceived school support, motivation and perceived use of contextual teaching. The continuous use of contextual teaching will benefit students and school generally because contextual teaching is an effective teaching approach that prepares students who can relate knowledge with actual real life problems and eventually will become expert human capital.